Hubungan Tingkat Pendidikan dan Pemahaman Masyarakat dengan Prevalensi Covid19 di Jawa Timur - Musa Ghufron (Universitas Muhammadiyah Surabaya, 2020)
AbstractIntroduction: Pandemic covid19 has entered Indonesia since the beginning of March 2020and resulted in many changes and reactions. Various impacts have been caused by theincreasing number of patients infected with covid19 which is increasingly significant. It isnecessary to make a quick and massif effort to prevent the higher covid19 transmission rate inIndonesia. Efforts to prevent covid19 transmission are in desperate need of active participationof the community to succeed to the maximum. A study is needed to find out the public'sunderstanding of covid19 disease so that efforts to increase people's participation in breakingthe chain of transmission can be more targeted and targeted.Method: This study uses quantitative methods by performing primary data analysis in the formof questionnaires in the form of google form and secondary data from the official website ofthe covid19 task force. The data was processed and tested to see the relationship betweeneducation level and understanding of covid19 disease to the number of covid19 cases using theminitab data processing app.Result: From the double logistic regression test obtained the value of the relationship betweena person's level of understanding of covid19 disease to the number of covid19 cases of 0.447and the relationship between the level of education to the number of covid19 cases of 0.303.Conclusion: There is no relationship between the level of understanding about covid19 diseaseand the level of education of a person to the number of covid19 cases in the community in eastJava province.Keywords: education, understanding, prevalence, covid19